2018
DOI: 10.1021/acs.iecr.8b02973
|View full text |Cite
|
Sign up to set email alerts
|

Optimization-Based Input/Output Linearizing Control Strategy for a pH Process with Multiple Titrant Streams

Abstract: This work develops a control strategy to handle coupling effects between the level and pH for a pH process with multiple titrant streams. The feedback controller is formulated based on a nonlinear optimization problem of an input/output (I/O) linearization for output tracking. In order to calculate the control actions and estimate the state disturbances simultaneously, an integrated disturbance estimator is combined into the developed control structure. The proposed controller is applied to control the outlet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Input/output (I/O) linearization is a model‐based control technique that provides the effectiveness of output tracking with a few required tuning parameters. The method has been extensively studied to handle various controller designs—including the process operation modes, minimum phase (MP)/nonminimum phase (NMP) behavior, or stable/unstable process . The I/O linearization method is typically applied for a process with an ordinary differential equation model with MP behavior, and it is later extended the concept to a class of partial differential equation system …”
Section: Introductionmentioning
confidence: 98%
“…Input/output (I/O) linearization is a model‐based control technique that provides the effectiveness of output tracking with a few required tuning parameters. The method has been extensively studied to handle various controller designs—including the process operation modes, minimum phase (MP)/nonminimum phase (NMP) behavior, or stable/unstable process . The I/O linearization method is typically applied for a process with an ordinary differential equation model with MP behavior, and it is later extended the concept to a class of partial differential equation system …”
Section: Introductionmentioning
confidence: 98%
“…In the application of adaptive control, past data should be discounted to have a good closedloop performance with respect to changes in process conditions. Srihawan et al 28 presented an I/O linearization control law based on nonlinear optimization for coupled control of pH and its solution level using multiple titrants. The operating cost of the pH plant increases with these control schemes, as there is always a need for multiple control units of this sort.…”
Section: Introductionmentioning
confidence: 99%
“…Westerink et al suggested that one‐dimensional mathematical model is quite reasonable to predict the hotspot formation inside a tubular reactor. Srihawan et al proposed a real‐time scheme to deal simultaneously with pH and level control of solution in a tank. They designed a linearized feedback controller for trajectory tracking.…”
Section: Introductionmentioning
confidence: 99%